Single Functional Index Quantile Regression for Functional Data with Missing Data at Random - Kadiri, Nadia; Mekki, Sanaà Dounya; Rabhi, Abbes (Właściwości asymptotyczne estymatorów półparametrycznych dla kwantyla warunkowego pojedynczego wskaźnika funkcjonalnego z losowymi brakami danych, 2023)
The primary goal of this research was to estimate the quantile of a conditional distribution using a semi-parametric approach in the presence of randomly missing data, where the predictor variable belongs to a semi-metric space. The authors assumed a single index structure to link the explanatory and response variable. First, a kernel estimator was proposed for the conditional distribution function, assuming that the data were selected from a stationary process with missing data at random (MAR). By imposing certain general conditions, the study established the model’s uniform almost complete consistencies with convergence rates.
Econometrics = Ekonometria, 2023, Vol. 27, No. 3, s. 1-19
Keywords: functional data analysis; funcional single index process; kernel estimator; missing at random; nonparametric estimation; small ball probability; funkcjonalna analiza danych; funkcjonalny proces pojedynczego indeksu; estymator jądra; losowe braki; estymacja nieparametryczna; prawdopodobieństwo małej kuli